Data justice: social work and a more just future. Issue 3 (3rd July 2021) - Goldkind, Lauri; Wolf, Lea; LaMendola, Walter
ABSTRACT: As new forms of data proliferate, data are increasingly used as a tool to determine access to resources, levels of sanction, and vulnerability to surveillance. Although the use of data to implement systematically biased policy is not new, the contemporary primacy of data across core institutions imposes disproportionate harms on already marginalized communities. Activist-proposed conceptual frameworks informed by the notion of data justice provide a basis to operationalize human rights in an evolving technoculture. This article urges social workers to recognize new data driven forms of inequality across individual, organizational, and community levels of practice, offering concrete examples of data harms and of just data practices that embody transparency, accountability, nondiscrimination, dignity, and participation.